From Fisheries to Fossil Fuel: (More) Lessons for WTO’s Role in Subsidy Reform - Venkataraman, Akshaya (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2025)
The article examines how the World Trade Organization (WTO) Fisheries Subsidies Agreement (FSA)—the first multilateral deal to discipline subsidies on environmental grounds—offers lessons for reforming fossil fuel subsidies (FFS). It argues that the WTO remains a relevant forum for such reform, combining legal expertise, institutional frameworks for transparency, and broad membership to support coordinated action. The discussion is organized around key lessons drawn from the FSA: adopting a phased approach to reform that builds momentum over time; fostering inter-institutional cooperation to integrate economic and environmental expertise; strengthening notification and reporting obligations to address the chronic lack of information surrounding FFS; and rethinking special and differential treatment, which has proved contentious, in favor of alternatives such as common but differentiated responsibilities. The article emphasizes that while challenges are considerable—including geopolitical tensions, energy security concerns, and the limits of the WTO’s current dispute settlement system—the FSA demonstrates that progress is possible. Building on its experience, multilateral cooperation under the WTO could help phase out fossil fuel subsidies and redirect resources toward a sustainable and equitable energy transition.